SISTEM PENANGANAN BANJIR TUKAD BUANA - Budiadi, I Made; Sutapa, I Nyoman; Parwita, I Gusti Lanang Made; Ramia, I Nyoman (Proceedings; Vol 1 No 1 (2020): Prosiding Seminar Nasional Ketekniksipilan Bidang Vokasional VIII, 2020)
The development of the population in the city of Denpasar has had an impact on the increase in new residential areas that replace the previous land functions of rice fields and fields that result in increased surface runoff. This increase in surface runoff has the potential to cause flooding and stagnant water at several points around the Buana river watershed which is a Mati river tributary located west of the Batu Kandik market in Denpasar City (Denpasar public work Office). The results of the design rainfall analysis show that design rain 2 (R2) year = 122.78 mm, R5 = 143 mm, R10 = 155.62 mm, R20 = 165.79, R25 = 179.98 mm, R50 = 182.12, R100 = 193.01 mm. Design flood analysis using a rational formula produces a cross-sectional plan with an average base width of 3 m and a height of 1-2 m. Improvement of the drainage system is done by widening the channel and dredging the base at several points blocked by trees, buildings and bedrock channels. The results of topographic analysis show that the right Buana river channel has a length of 1385.56 m and the left Buana river channel has a length of 1623.58 m. With the new channel dimensions, the analysis shows that it will be able to drain the maximum discharge after a 25-year return.